PRINSIF ITIKAD BAIK DALAM SUATU KONTRAK - Warmiyana Zairi Absi; Rusniati Rusniati (Justici, 2022)
In civil law the principle of good faith is a rule contained in an agreement, either an agreement between an individual and an individual or an individual with a legal entity. As contained in Article 1338 paragraph (3) of the Civil Code (hereinafter referred to as the Civil Code) it is stated that: "An agreement must be carried out in good faith." The meaning of good faith here is to act as a good person. Understanding of good faith, presumably business people in carrying out their activities should not harm other parties and do not take advantage of other parties to benefit themselves. Thus the contract is not only determined by the words formulated by the parties, but the judge can intervene in the freedom of contract by basing it on the principle of good faith, interpreting the contents of the contract beyond the words listed (may be added, expanded), even the contents can be determined. against those words. Therefore, it is not only determined by the words formulated by the parties, but also by justice and good faith.